Boiling Heat Transfer and Droplet Spreading of Nanofluids - Sohel Murshed, S.M.; Nieto de Castro, C.A. (Recent Patents on Nanotechnology, 2013)
Nanofluids- a new class of heat transfer fluids have recently been a very attractive area of research due to their fascinating thermophysical properties and numerous potential benefits and applications in many important fields. However, there are many controversies and inconsistencies in reported arguments and experimental results on various thermal characteristics such as effective thermal conductivity, convective heat transfer coefficient and boiling heat transfer rate of nanofluids. As of today, researchers have mostly focused on anomalous thermal conductivity of nanofluids. Although investigations on boiling and droplet spreading are very important for practical application of nanofluids as advanced coolants, considerably fewer efforts have been made on these thermal features of nanofluids. In this paper, recent research and development in boiling heat transfer and droplet spreading of nanofluids are reviewed together with summarizing most related patents on nanofluids published in literature. Review reveals that despite some inconsistent results nanofluids exhibit significantly higher boiling heat transfer performance compared to their base fluids and show great promises to be used as advanced heat transfer fluids in numerous applications. However, there is a clear lack of in-depth understanding of heat transport mechanisms during phase change of nanofluids. It is also found that the nanofluids related patents are limited and among them most of the patents are based on thermal conductivity enhancement and synthesising processes of specific type of nanofluids.
Keywords: nanofluids